Model Prediksi Kemenangan Tim dalam Game League of Legend Menggunakan Algoritma Decision Tree - Green Arther Sandag (Jurnal Komputer Terapan, 2021)
Online games are growing very rapidly because they are supported by the development of smart phones which are increasingly being used. Online games are in great demand by various groups ranging from children, teenagers to adults who enjoy playing online games. The purpose of this research is to predict the team's victory in the league of legend game by using the decision tree algorithm. In this research, the dataset taken is 50,000 data, divided into 80% training and 20% testing. The results of this research show that the Decision Tree Algorithm has the best performance among other algorithms to predict victory with the results of 96.42% accuracy, 97.74% recall Team 1, 95.06% recall Team 2, 95.31% precision Team 1, 97.62% precision Team 2 and 0.157 RMSE for independent results while for 10 fold cross validation results have 96.24% accuracy, 97.34% recall Team 1, 95.11% recall Team 2, 95.33% precision Team 1, 97.21% precision Team 2, and 0.161 RMSE in detecting wins in the game League of Legend.